2017
DOI: 10.1002/ijc.31078
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel lymph node biopsy versus observation in thick melanoma: A multicenter propensity score matching study

Abstract: The clinical value of sentinel lymph node (SLN) biopsy in thick melanoma patients (Breslow >4 mm) has not been sufficiently studied. The aim of the study is to evaluate whether SLN biopsy increases survival in patients with thick cutaneous melanoma, and, as a secondary objective, to investigate correlations between survival and lymph node status. We included 1,211 consecutive patients with thick melanomas (>4 mm) registered in the participating hospitals' melanoma databases between 1997 and 2015. Median follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…Keywords: melanoma, sentinel lymph node biopsy, complete lymph node dissection, prognosis Nevertheless, several studies have shown that SLN biopsy is useful in the prognostic stratification of patients with thick melanoma [2]. This, together with its value when selecting patients for new adjuvant treatments [3,4] means the procedure is still valid.…”
Section: Resultsmentioning
confidence: 99%
“…Keywords: melanoma, sentinel lymph node biopsy, complete lymph node dissection, prognosis Nevertheless, several studies have shown that SLN biopsy is useful in the prognostic stratification of patients with thick melanoma [2]. This, together with its value when selecting patients for new adjuvant treatments [3,4] means the procedure is still valid.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of regional metastasis is a predictor of worse survival in thick melanoma 1 and is currently an indication for adjuvant therapy. Few studies have analysed the prognostic role of clinical and pathologic variables in thick melanoma without metastatic lymph node involvement.…”
Section: Editormentioning
confidence: 99%
“…Editor, Frontal fibrosing alopecia (FFA) is a primary cicatricial alopecia characterized by a progressive recession of the frontotemporal hairline with frequent involvement of eyebrows. 1 FFA is more frequent in postmenopausal women, but it is increasingly diagnosed among premenopausal women and men. 2 Hair involvement is also common in other sites like eyelashes, extremities and axillae.…”
Section: Editormentioning
confidence: 99%
See 1 more Smart Citation
“…Systemic inguinofemoral lymphadenectomy is considered a standard surgical procedure for vulvar SCC patients with >1 mm depth of invasion. Currently, lymphatic mapping and subsequent sentinel lymph node biopsy (SLNB) is the standard procedure in early-stage breast cancer and melanoma 8 , 9 . The incidence of inguinofemoral lymph node involvement for early-stage invasive vulvar SCC with clinically node negative is less than 30%; therefore, inguinofemoral lymphadenectomy could be omitted in about 70% of those patients, making SLNB an acceptable method in the management of early-stage vulvar SCC with negative groin nodes 10 - 12 .…”
Section: Introductionmentioning
confidence: 99%